Efeito da adubação potássica e da época de colheita na produtividade de canola - Rossetto, C. A. V. (1998)
A field experiment was carried out to study the effects of potassium fertilization and time of harvesting on canola seed yield. The soil was a Red-Yellow Latosol (Hapludox), and the experimental design was a subplot replicated four times in completely randomized blocks. Potassium levels (0 and 40 kg ha-1 of K) were applied in the plots, and the subplots consisted of 7 weekly harvests, starting 112 days after planting. Yield and yield components were evaluated at each harvest. Although no positive effect of potassium fertilization on seed yield and growth parameters was evident, this fertilization caused higher retention of pods from the harvest at 147 and 154 days after planting. Time of harvesting did not affect seed yield. The maximum level of dry matter of the above ground part of the plants was obtained from the harvest at 112 days, and, of seeds, at 126 days, at high potassium level.